Mapping soil compaction using indicator kriging in Santa Fe province, Argentina - Carlos Agustín Alesso; María Eugenia Carrizo; Silvia del Carmen Imhoff (Acta Agronómica)
Soil compaction is a complex physical process that affects the crop performance by limiting the expansion of the roots and the reduction of water and nutrients uptake from soil. Due to the spatial variability of soil compaction, the needs for remedial practices may vary within the field. However, mapping soil compaction estimated by cone index (CI) data is a difficult task. The aim of this study were to examine the spatial variability of CI data in a fine-mixed-thermic Typic Argiudoll soil form the center of Santa Fe, province -Argentina under no-till system, and to delineate zones for site-specific tillage based on maps of probabilities of occurrence of soil compaction developed using indicator kriging. Sixty nine georeferenced CI and volumetric water content (SWC) measurements were recorded in a 70 x 110 m experimental area. Sample locations were distributed following a pseudo-regular grid avoiding visible machinery footprint. An indicator variable was created by splitting the sampling locations into two groups based on the CI profiles within 0-30 cm depth. The spatial structure of the CI data aggregated by 10-cm layers and the indicator variable was assessed by a model-based approach. The high variability and poor spatial structure observed in CI data was attributed to the effect of tillage and traffic under the sampling scale. This feature underpinned the application of spatial interpolation techniques for this property. However, maps of the probability of occurrence of soil compaction in the root zone were be obtained by integrating the cone index data of the arable horizon (0-30 cm) using the indicator kriging approach. Such probability maps could be useful for the delineation of potential zones for site-specific tillage.